Directing - Wexman, Virginia Wright (New York: I.B.Tauris, 2017)
Of all the artisans who work in the American film industry, directors have been given the lion's share of attention. Yet few books in this literature address the ways directors have worked with others and have negotiated the constraints and opportunities posed by a complex production process and a sprawling commercial industry. Directing fills this gap. It provides the historical context necessary to understand the key role of directors in the Hollywood system. It covers iconic directors like Cecil B. DeMille, Francis Ford Coppola and Terrence Malik. It also shows how a selection of remarkable filmmakers confronted issues encountered during a given period; for example, how Ida Lupino negotiated 1950s ingrained sexism and how black directors like Charles Burnett operated in the system. It follows the working strategies of independents like Steven Soderbergh or Tim Burton and of directors dealing in twenty-first century digital cinema. Both readable and detailed, the book has appeal across the study of film and film production to the broader interest in the director's art.
Includes bibliographical references (pages 161-187) and index.
Keywords: Artet boterore; Arti skenik-kinematografia; Fimi; Motion pictures -- Production and direction-produksioni-regjia -- California -- Los Angeles; Motion pictures -- Production and direction; California -- Los Angeles. -- Hollywood; Filmi-regjizoret-producente-vitet 1895-1927 -historia-analiza; Hollivudi -filmi klasik-filmi pas lufte-vitet 1947-1967-filmi modern-vitet 1968-1980; Filmi bashkekohor-vitet 2000-